2013
DOI: 10.1002/poc.3118
|View full text |Cite
|
Sign up to set email alerts
|

The 3,5‐dinitroanilide anion: a singlet anilide anion with evidence for a thermally accessible triplet state

Abstract: Anilide anions derived from deprotonation of 4-nitroaniline and 3,5-dinitroaniline were examined by using DFT calculations, as well as ultraviolet and 1 H NMR experiments. The calculations indicate that the free anions are ground state singlets. However, when coordinated to a Li counterion, the 3,5-dinitroanilide anion is predicted to have a very narrow gap between the singlet and the triplet state. Spectroscopic data is consistent with this prediction. The UV-Vis spectrum of this anion shows a maximum absorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Depending on the system, the open‐shell triplet state was found to be either the ground state, or to be negligibly higher in energy than the closed‐shell singlet. The diradical state is stabilized by cation binding to the nitro group (Figure ) …”
Section: Fluctuating Ground‐state Multiplicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the system, the open‐shell triplet state was found to be either the ground state, or to be negligibly higher in energy than the closed‐shell singlet. The diradical state is stabilized by cation binding to the nitro group (Figure ) …”
Section: Fluctuating Ground‐state Multiplicitymentioning
confidence: 99%
“…The diradical state is stabilized by cation binding to the nitro group (Figure 8). 54,55 The change from the closed-shell singlet into a triplet ground state, and hence magnetization, has been shown to occur as a result of protonation and/or oxidation in a number of systems. For instance, a diradical was formed by double protonation and subsequent intramolecular electron transfer from donor to acceptor unit, as shown in Figure 9(a).…”
Section: Exciting Casesmentioning
confidence: 99%
“…Using ultraviolet and 1 H NMR experiments, Perrotta and Falvey (2013) characterized several ion-diradicals with low energy triplet states. Although not predicted to be the ground state, the authors found that sufficiently strong electron-withdrawing groups could lower the energy of the triplet state enough to create a population of triplet anilide (imide) anions.…”
Section: S C H E M Ementioning
confidence: 99%
“…While nitrene anions are difficult to isolate in solution, they are known to take part in condensed phase chemistry (Herbranson & Hawley, 1990; Murata et al, 1995; Van Galen et al, 1986). They fall into a category of organic molecules with low‐lying high‐spin electronic states that have drawn significant interest for many years because of their unique electronic properties (Perrotta & Falvey, 2013). Because of their high reactivity, they are difficult to characterize.…”
Section: Condensed‐phase Nitrene Anionsmentioning
confidence: 99%